In Silico Studies of Bioactive Compounds from Pseudomonas azotoformans UICC B-91 in Inhibiting Candida albicans - Rina Hidayati Pratiwi; Endang Sulistyaniningsih; Jumadi Jepri (Jurnal Biodjati, 2024)
Futoamide, Gentialutine, Gentiabetine, 1-[(2E,4E)-2,4-dec- adienoyl] pyrrolidine, Lycopodine, Dihydro-lycopodine are bioactive compounds that can be obtained Pseudomonas azotoformans UICC B-91. Previous research results indicate that P. azotoformans extract- ed with dichloromethane, chloroform, and ethyl acetate have antican- didal activity against Candida albicans ATCC 10231. C. albicans is considered to become an opportunistic pathogen and well-known as the main cause of candidiasis. This study aims to determine the mech- anism of inhibition of bioactive compounds from P. azotoformans UICC B-91 on the growth of C. albicans using the molecular docking method. Docking was carried out using the targeted (Lanosterol 14 alpha demethylase and Glucan endo-1,3-beta-D-glucosidase) dock- ing method with an exhausted parameter of 50. The size of the grid- box was adjusted to the position of the amino acid residues based on predictions of binding sites using PrankWeb. The docking results were obtained in the form of binding affinity resulting from the inter- action of the compound with the protein. Results showed that the three sample compounds had the potential to form strong and stable bonds with both protein targets with only two ligands show a binding energy value of less than -7 kcal/mol. In addition, the speed and stability of the bond between the sample and the target protein cannot exceed control ligands, thus it can be predicted the structure of ligand. Fu- toamide, 1-[(2E,4E)-2,4-decadienoyl] pyrrolidine, Lycopodine, and Dihydrolycopodine had binding potential with Lanosterol 14 alpha demethylase. For Glucan endo-1,3-beta-D-glucosidase, only Fu- toamide had the potential to form stable and strong bonds that similar to the control. It can be concluded that the futoamide, one of ligand from P. azotoformans compounds has the potential as a multitarget inhibitor of the two C. albicans proteins, because it has various affini- ties and interaction stability for Lanosterol 14 alpha demethylase and Glucan endo-1,3-beta-D-glucosidase.